Reliability and validity of the Turkish version of the teachers’ basic ICT competence beliefs scale - Charlott Rubach; Pınar Korukluoğlu; Bülent Alcı (International Journal of Assessment Tools in Education)
The present study seeks to adapt the Teachers’ Basic Information Communication Technology (ICT) Competence Beliefs Scale, developed by Rubach and Lazarides (2021), into Turkish and test the adapted scale's validity and reliability. The initial step involved conducting a linguistic equivalence of the scale from English to Turkish with 62 English language teachers in a pre-test. Subsequently, the Turkish version of the scale was administered to 356 teachers (69.7% female, 30.3% male) in Turkey to assess its validity and reliability. Participating teachers were from different subjects (e.g., 9.8% science, 7.9% mathematics, 3.7% social science) and school types (27.5% primary school, 55.3% secondary school, 17.1% others). Results of confirmatory factor analysis indicated the original six-factor structure with three first-order and three second-order factors that best fitted the data. The same competence dimensions were indicated in the Turkish contexts as in the original instrument, i.e., information and data literacy; communication and collaboration; digital content creation; safety and security; problem-solving; analyzing and reflecting. The correlations between all six first-order factors were between .58 ≥ r ≥.79. All factors showed good reliability indices, i.e., α > .83, ω > .83 and CR > .72. The adapted instrument was found to be invariant across gender. Mean-level differences among gender groups point to one difference with male teachers reporting higher competence beliefs for digital content creation compared to female teachers. In conclusion, the results of this replication study support the cross-cultural transferability of the original Teachers' Basic ICT Competence Beliefs instrument developed by Rubach and Lazarides (2019).